Association of Country-Specific Socioeconomic Factors With Survival of Patients Who Experience Severe Classic Acute Graft-vs.-Host Disease After Allogeneic Hematopoietic Cell Transplantation. An Analysis From the Transplant Complications Working Party of the EBMT - Frankiewicz, Andrzej; Peczynski, Christophe; Giebel, Sebastian; Harrington, Alenca; Socié, Gerard; Niederwieser, Dietger; Scheid, Christoph; Bornhäuser, Martin; Kröger, Nicolaus; Elmaagacli, Ahmet; Afanasyev, Boris; Dreger, Peter; et al. (Frontiers in Immunology, 2020)
Acute graft-vs.-host disease (aGvHD) is one of the most frequent causes of transplant-related mortality (TRM) after allogeneic hematopoietic cell transplantation (alloHCT). Its treatment is complex and costly. The aim of this study was to retrospectively analyze the impact of country-specific socioeconomic factors on outcome of patients who experience severe aGvHD. Adults with hematological malignancies receiving alloHCT from either HLA-matched siblings (n = 1,328) or unrelated donors (n = 2,824) developing grade 3 or 4 aGvHD were included. In univariate analysis, the probability of TRM at 2 years was increased for countries with lower current Health Care Expenditure (HCE, p = 0.04), lower HCE as % of Gross Domestic Product per capita (p = 0.003) and lower values of the Human Development Index (p = 0.02). In a multivariate model, the risk of TRM was most strongly predicted by current HCE (HR = 0.76, p = 0.006). HCE >median was also associated with reduced risk of the overall mortality (HR 0.73, p = 0.0006) and reduced risk of treatment failure (either relapse or TRM; HR 0.77, p = 0.004). We conclude that country-specific socioeconomic factors, in particular current HCE, are strongly associated with survival of patients who experience severe aGvHD.